Formulasi dan Evaluasi Sediaan Gel Nanopartikel Ekstrak Temulawak (Curcuma xanthorrhiza) sebagai Tabir Surya - Anjas wilapangga; Deni Rahmat; Rachmaniar Rachmaniar (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Temulawak (Curcuma xanthorrhiza) is known as a plant that has many health benefits, including antibacterial, anti-inflammatory, antidiabetic and anticancer. The purpose of this study was to formulate a gel preparation containing temulawak extract nanoparticles as a sunscreen. The gel formed must be evaluated physically including: organoleptic, homogentias, viscosity and spreadability, as well as pH test and SPF examination. Temulawak extract, Nanocurcumin manufacturing method using ionic gelation characterized using particle size analyzer. Results showed that temulawak extract gel and temulawak extract nanoparticle gel did not change color and remained in a homogeneous state. The viscosity of temulawak extract gel is 25098 cPs, while temulawak extract nanoparticle gel is 25673 cPs. The spreading ability of temulawak extract gel was 6.3 cm while the temulawak extract nanoparticle gel formula was 6.5 cm. The pH value of the temulawak extract gel was 5.61 while the pH value of the temulawak extract nanoparticle gel was 5.47. The SPF value of temulawak extract gel was 16.77 while that of temulawak nanoparticle gel was 19.88. Thus, temulawak extract nanoparticle gel can have potential as a sunscreen gel.